2016
DOI: 10.3389/fphar.2016.00108
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effects of Gamma-Irradiation for Decontamination of Medicinal Cannabis

Abstract: In several countries with a National medicinal cannabis program, pharmaceutical regulations specify that herbal cannabis products must adhere to strict safety standards regarding microbial contamination. Treatment by gamma irradiation currently seems the only method available to meet these requirements. We evaluated the effects of irradiation treatment of four different cannabis varieties covering different chemical compositions. Samples were compared before and after standard gamma-irradiation treatment by pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 29 publications
1
48
0
4
Order By: Relevance
“…This may be achieved at multiple points in the production process; by ensuring clean growing media, handling and storing preparations hygienically, and gamma‐irradiation of the final product . Gamma‐irradiation has been tested successfully as a standard technique for sterilization of medicinal cannabis preparations .…”
Section: Resultsmentioning
confidence: 99%
“…This may be achieved at multiple points in the production process; by ensuring clean growing media, handling and storing preparations hygienically, and gamma‐irradiation of the final product . Gamma‐irradiation has been tested successfully as a standard technique for sterilization of medicinal cannabis preparations .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, McKernan et al (2016b) reported the presence of mould and yeast in 6/17 dispensary-derived cannabis bud samples using qPCR, which also included several Penicillium species. One approach to reducing these fungal contaminants on cannabis buds is the prescribed use of post-harvest gamma-irradiation (Meklin et al, 2007;Hazekamp, 2016), which is currently being implemented by some licensed producers in Canada (https:// aphria.ca/blog/3-facts-about-medical-cannabis-irradia tion/). Powdery mildew on hemp was previously reported to be caused by Leveillula taurica (Lev.)…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, while desiccation of the flowers and high temperature would be expected to decrease viable microbial counts, it would not eliminate all of the microorganisms nor the endotoxins and mycotoxins that they would produce (or have already produced). Gamma irradiation, where material is exposed to a high powered gamma radiation source, is another approved method by Health Canada (https://www.canada.ca/) for decontamination which does not cause changes in the content of THC and CBD but does alter terpene quality slightly [49]. The amount of gamma radiation used is calibrated to be sufficient to cause enough DNA damage such that no cells remain viable.…”
Section: Indoor Cultivation and Storage Of Cannabis Are Propitious Tomentioning
confidence: 99%